# Prove the identity: (cos x / (1-sin x)) - tan x = 1/cos x

### 2 Answers | Add Yours

Prove the identity `cosx/((1-sinx))-tanx=1/cosx` :

`cosx/((1-sinx))-tanx`

`=cosx/((1-sinx))-sinx/cosx` trig substitution identity

`=(cos^2x-sin(x)(1-sinx))/(cosx(1-sinx))` Add fractions (common denominator)

`=(cos^2x+sin^2x-sinx)/(cosx(1-sinx))` Distributive property;rearrange terms

`=(1-sinx)/(cosx(1-sinx))` Pythagorean identity

`=1/cosx` Cancel like factors

QED.

**Sources:**

It has to be proven that `(cos x / (1 - sin x)) - tan x = 1/cos x`

`(cos x / (1 - sin x)) - tan x`

=> `(cos x / (1 - sin x)) - (sin x/cos x)`

=> `(cos^2x - (1 - sin x)*sin x)/((1 - sin x)*cos x)`

=> `(cos^2x - sin x + sin^2 x)/((1 - sin x)*cos x)`

=> `(1 - sin x)/((1 - sin x)*cos x)`

=> `1/cos x`

**This proves that `(cos x / (1 - sin x)) - tan x = 1/cos x` **